Improving Students’ Motivation to Collaborate Using Instagram: An Action Research in SMAN 1 Depok Yogyakarta - Putri, Theresia Febi Amanda; Kastuhandani, Fidelis Chosa (International Journal of English Education and Linguistics (IJoEEL), 2023)
This research aimed to show how Instagram could be used to improve students' motivation to collaborate and how discussing with friends could influence their motivation to be involved in collaborating. This research was conducted knowing that the students’ low motivation in collaboration impacted their activeness in class participation, work results, and low quality of social interactions. This study was classroom action research in two Grade 11 classes as the actual action sites. To collect the data, the researchers interviewed six students in both classes. The ARCS Model by Keller (2023) was used as a framework to answer the research questions: ‘How can Instagram be used to enhance students' collaboration motivation in an interactive online discussion forum? and ‘How can discussions with friends on social media influence student motivation and involvement in collaborative English language learning? The framework was chosen because it was designed to increase students' learning motivation and focused on attention, relevance, confidence, and satisfaction. This study found that Instagram could improve students’ motivation to collaborate in online discussion forums. Further, the platform transformed passive participants or shy students into active participants to were involved in class collaborations.